Religiosity in Indonesian Language Textbooks for Elementary School - Zaka, Istifatun; Maharani, Kiki (Borneo International Journal of Islamic Studies, 2024)
This study aims to describe the existence of religiosity values in Indonesian language textbooks for elementary school (Sekolah Dasar/SD). The type of this study is qualitative with content analysis. The source of study is Bahasa Indonesia textbooks for elementary schools in the online version in Kurikulum Merdeka with four samples, namely “Bahasa Indonesia: Aku Bisa!” for SD Class I, “Bahasa Indonesia: Keluargaku Unik” for SD Class II, “Bahasa Indonesia: Lihat Sekitar for SD Class IV, and “Bahasa Indonesia: Bergerak Bersama” for SD Class V. The data are in the form of words, phrases, sentences, or paragraphs that contain interpersonal meaning and character value content. The researcher serves as a human instrument, employing techniques for data collection such as active listening and note-taking as follow-up methods. The study's findings are presented as follows: religiosity values were realized through gratitude for The Supreme One's grace and good morals or behavior.